2007
DOI: 10.1080/10412905.2007.9699309
|View full text |Cite
|
Sign up to set email alerts
|

Clastogenic and Anticlastogenic Effect of the Essential Oil fromCasearia sylvestrisSwart.

Abstract: The essential oil composition obtained from the leaves of Casearia sylvestris has been investigated by GC and GC/MS. Thirty-seven compounds were identified in the oil. The major constituents of which were β-caryophyllene (27.5%) and bicyclogermacrene (24.2%). The clastogenic and anticlastogenic effect of the oil was tested by chromosome aberration in cells of tissue hepatoma of Rattus novergicus.The three different concentrations of C. sylvestris oil showed clastogenic effects. However, in the tests of anticla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 7 publications
1
12
0
2
Order By: Relevance
“…Monoterpenes can also be identified, but not in significant amounts (Sousa et al 2007, Stefanello et al 2010. The potential of terpenes for the treatment of candidiasis has been reported previously (Dalleau et al 2008, Martínez et al 2014 In the present work it was observed that both pure essential oil and fraction 1-6 are rich in non-oxygenated and oxygenated sesquiterpenes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Monoterpenes can also be identified, but not in significant amounts (Sousa et al 2007, Stefanello et al 2010. The potential of terpenes for the treatment of candidiasis has been reported previously (Dalleau et al 2008, Martínez et al 2014 In the present work it was observed that both pure essential oil and fraction 1-6 are rich in non-oxygenated and oxygenated sesquiterpenes.…”
Section: Discussionsupporting
confidence: 66%
“…The essential oils of this genus are rich in monoterpenes and sesquiterpenes (Tininis et al 2006, Sousa et al 2007, Silva et al 2008, Pereira et al 2017, and some of the main compounds already identified are α-zingiberene, α-humulene, caryophyllene, and bicyclogermacrene (Esteves et al 2005, Bou et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The main constituents were germacrene D (18.6%), E-caryophyllene (14.7%), δ-cadinene (6.2%), and α-cadinol (5.4%). The predominance of sesquiterpene hydrocarbons in the leaves essential oil of Casearia species has been previously observed (Stefanello et al, 2010;Silva et al, 2008;Sousa et al, 2007;Schneider et al 2006;Esteves et al, 2005;De Morais et al, 1997). In particular, E-caryophyllene was found in all samples as a main component (more than 10%).…”
Section: Resultsmentioning
confidence: 63%
“…The essential oils of Casearia spp analyzed to date are rich in sesquiterpenes (De Morais et al, 1997;Esteves et al, 2005;Schneider et al, 2006;Sousa et al, 2007;Silva et al, 2008;Stefanello et al, 2010) and one sample showed cytotoxic activity (Silva et al, 2008). Casearia lasiophylla Eichler, known as "guaçatunga-graúda" is a tree native from Brazil for which no chemical or pharmacological evaluation has previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian Agency of Medicines (Agência Nacional de Vigilância Sanitária -ANVISA) recognizes the importance of the species that was included in a positive list of medicinal plants for sale in pharmacies (Brasil 2010). Secondary metabolites isolated/identified from C. sylvestris include monoterpenes and sesquiterpenes (Sousa et al 2007), nor-isoprenoids (Santos 2008, Wang et al 2009a, triterpenes, lapachol, cafeic, chlorogenic and vanillic acids, flavonoids (Raslan et al 2002), neolignans (Wang et al 2010), ellagic and gallic acids derivatives (Silva et al 2008a, Silva et al 2008b. Additionally, phytochemical studies of Casearia species have revealed the presence of typical oxygenated tricyclic cis-clerodane diterpenes in which the tetrahydrofuran ring bears two acyloxy groups at C18 and C19 (Chen and Wiemer 1991, Guittet et al 1988, Kanokmedhakul et al 2005, Oberlies et al 2002.…”
Section: Introductionmentioning
confidence: 99%